The Leadership of the Prophet: The Role Model of Today's Leaders - Eka Safitri; Muhammad Fatih Abdurrahman; Putri Fajriatin Qona'ah; Wahyu Nur Aini (Assosiation of Islamic Education Lecturer of Universitas Jenderal Soedirman, 2021)
In fact, every human being is a leader, either for himself or for others. The nature of leadership is closely related to a leader. Leadership is a trait that can influence, move or encourage others to achieve a predetermined goal. The essence of leadership in Islam leads a servant to true servitude to Allah. In Islam, a leader must be an example for his group, such as the Prophet Muhammad saw. The personality of the Prophet Muhammad saw. as a leader is exemplary because of his toughness which is not affected by the circumstances of the surrounding community which are still ignorant. This study aims to analyze the leadership style of the Prophet Muhammad that can be applied today. The data collection technique used reading and note-taking techniques and the data were analyzed using a qualitative descriptive. From the results of this study, it can be explained that the leadership style of the Prophet Muhammad that can be applied today is a democratic attitude. This study concludes that the Prophet Muhammad is a role model for leaders, even today leaders should apply the leadership style of the Prophet Muhammad who is religiously democratic.